2013
DOI: 10.1073/pnas.1309324111
|View full text |Cite
|
Sign up to set email alerts
|

Ohnologs are overrepresented in pathogenic copy number mutations

Abstract: A number of rare copy number variants (CNVs), including both deletions and duplications, have been associated with developmental disorders, including schizophrenia, autism, intellectual disability, and epilepsy. Pathogenicity may derive from dosage sensitivity of one or more genes contained within the CNV locus. To understand pathophysiology, the specific disease-causing gene(s) within each CNV need to be identified. In the present study, we test the hypothesis that ohnologs (genes retained after ancestral who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 74 publications
(58 reference statements)
4
45
1
Order By: Relevance
“…Our fine‐tuned evolutionary rate analysis revealed that few PD genes were positively selected in the human lineage, which differs from the results of a previous study (Crespi et al ), and that PD genes are generally conserved as previous studies show (McLysaght et al ; Ogawa and Vallender ). However, the three detected PD‐PSGs ( CLSTN2, FAT1 , and SLC18A1 ), exhibited the unique signature of diversifying selection, estimated from the MK test and the DoS statistic.…”
Section: Resultscontrasting
confidence: 99%
“…Our fine‐tuned evolutionary rate analysis revealed that few PD genes were positively selected in the human lineage, which differs from the results of a previous study (Crespi et al ), and that PD genes are generally conserved as previous studies show (McLysaght et al ; Ogawa and Vallender ). However, the three detected PD‐PSGs ( CLSTN2, FAT1 , and SLC18A1 ), exhibited the unique signature of diversifying selection, estimated from the MK test and the DoS statistic.…”
Section: Resultscontrasting
confidence: 99%
“…These findings are to some extent supported by studies focusing on vertebrate genomes in which differences have been noted between genes resulting from whole-genome duplication events vs. single gene duplication events (Makino and McLysaght 2010;Dickerson and Robertson 2012;Singh et al 2012Singh et al , 2014McLysaght et al 2014). Indeed, genes resulting from whole-genome duplications are overrepresented in pathogenic vs. nonpathogenic copy number variants in humans (McLysaght et al 2014).…”
Section: Lessons From An X-chromosome Screenmentioning
confidence: 62%
“…Indeed, genes resulting from whole-genome duplications are overrepresented in pathogenic vs. nonpathogenic copy number variants in humans (McLysaght et al 2014). Therefore, whether an essential fly gene has multiple or single human homologs is important for its potential role in disease.…”
Section: Lessons From An X-chromosome Screenmentioning
confidence: 99%
“…The pathogenicity of the MYH11 duplication in the presented family is not proven, in spite of suggestive evidence for an association of this duplication with arterial dissection (Kuang et al., ; Grond‐Ginsbach, Chen, et al., ). The observation that the duplication at 16p13.1 encompasses four ohnologs ( NDE1, MYH11, ABCC1, and ABCC6) further suggests its pathogenicity, because ohnologs were shown to be dose‐sensitive and overrepresented in pathogenic copy number variation (Makino & McLysaght, ; McLysaght et al., ; Tropeano et al., ).…”
Section: Discussionmentioning
confidence: 99%